A case report of laboratory-acquired diphtheria - Geiss, Heinrich K.; Kiehl, Wolfgang; Thilo, Waltraud (Eurosurveillance, 1997)
In March 1996, when a 41 year old laboratory technician developed malaise, low grade fever, sore throat, hoarseness and dysphagia she was initially treated symptomatically. One day later, the patient was seen in the emergency room of an ear, nose, and thr
Gesehen am 31.03.2025